2013
DOI: 10.1016/j.scitotenv.2012.10.063
|View full text |Cite
|
Sign up to set email alerts
|

Derivation of a fuzzy national phosphorus export model using 84 Irish catchments

Abstract: ► Develops a new national phosphorus export model for agricultural catchments in Ireland ► Improves on earlier empirical phosphorus export models by using k-means clustering method for partitioning data ► Uses ANFIS model to predict annual average ortho-phosphorus concentrations using catchment characteristics ► Phosphorus desorption index (PDI) and runoff risk index (RRI) are essential predictors in the model. a b s t r a c t a r t i c l e i n f o Implementation of appropriate management strategies to mitigat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2013
2013
2015
2015

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 22 publications
(24 reference statements)
0
1
0
Order By: Relevance
“…Previous studies have suggested that, due to the lack of consideration of the mechanism and process of NPS pollution, Johnes' classical ECM is insensitive to changes in rainfall, topography, land use, land management, and other factors, and is thus only applicable to regions with a uniform distribution of rainfall, at terrain, and steady land use and management. 25,26 Given the spatially varying topography, climate, vegetation and other conditions of the TGRR, pollutant load simulations using the classical ECM usually fail to produce accurate results. The development process of NPS pollution could be simplied to the process of surface production and interception pollution.…”
Section: Modication Of the Export Coefficient Modelmentioning
confidence: 99%
“…Previous studies have suggested that, due to the lack of consideration of the mechanism and process of NPS pollution, Johnes' classical ECM is insensitive to changes in rainfall, topography, land use, land management, and other factors, and is thus only applicable to regions with a uniform distribution of rainfall, at terrain, and steady land use and management. 25,26 Given the spatially varying topography, climate, vegetation and other conditions of the TGRR, pollutant load simulations using the classical ECM usually fail to produce accurate results. The development process of NPS pollution could be simplied to the process of surface production and interception pollution.…”
Section: Modication Of the Export Coefficient Modelmentioning
confidence: 99%